2004
DOI: 10.1167/4.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Slant from texture and disparity cues: Optimal cue combination

Abstract: How does the visual system combine information from different depth cues to estimate three-dimensional scene parameters? We tested a maximum-likelihood estimation (MLE) model of cue combination for perspective (texture) and binocular disparity cues to surface slant. By factoring the reliability of each cue into the combination process, MLE provides more reliable estimates of slant than would be available from either cue alone. We measured the reliability of each cue in isolation across a range of slants and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
454
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(493 citation statements)
references
References 46 publications
32
454
2
5
Order By: Relevance
“…More broadly, this can be understood in terms of optimal cue combination approaches to perception (e.g. Hillis, Watt, Landy, & Banks, 2004;Jacobs, 2002;Knill & Saunders, 2003), and is also consistent with other proposals that recognition may involve both image-based and structural description representations (e.g., Foster & Gilson, 2002;Hummel, 2013;Hummel & Stankiewicz, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…More broadly, this can be understood in terms of optimal cue combination approaches to perception (e.g. Hillis, Watt, Landy, & Banks, 2004;Jacobs, 2002;Knill & Saunders, 2003), and is also consistent with other proposals that recognition may involve both image-based and structural description representations (e.g., Foster & Gilson, 2002;Hummel, 2013;Hummel & Stankiewicz, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…Several works have reported that humans perform near-optimal cue integration in a variety of settings (1)(2)(3)(4)(5)(6)(7)(8). It is, therefore, essential that the combination of inputs that leads to the multiplicative rule in an attractor network also results in optimal cue integration.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, humans can perform these inferences optimally, as in multi-cue or multisensory integration (1)(2)(3)(4)(5)(6)(7)(8). For complex tasks, such as object recognition, action perception, and object tracking, the computations required for optimal inference are intractable, which implies that humans must use approximate inferences (9)(10)(11).…”
mentioning
confidence: 99%
“…It is well known that the visual system can use these texture compression cues to estimate 3D shape (1)(2)(3)(4)(5)(6)(7)(8)(9). What is not known, however, is how the visual system measures the compression at each point in the image.…”
mentioning
confidence: 99%